(untitled) (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2017)
Background: Neck pain and back pain are the first cause of years lived with disability according to Global Burden of the Disease. Neck pain field do not have studies focused on identifying the gaps or the emerging, never or poorly addressed opportunities in this field. Objective: To identify and rank the neck pain research priorities, building a new agenda for primary care research on neck pain. Methods: A three round modified- Delphi survey was conducted. 400 experts in the field of neck pain research were identified thought search strategies at Expertscape and PubMed websites. The first round aimed to identify what are the most important primary care relevant questions that neck pain researchers should address. All responses were collated forming a list of research priorities. This list of research priorities was classified and ranked during the second and third rounds. The participants were also asked to identify which of the low back priorities formulated in the X International Forum for Primary Care Research can be also considered as neck pain research priority (Approval of the Ethics committee number 1294787). Results: Total of 115 agreed to participate in this study. The top 5 research priorities were: 1) to identify effectiveness and cost-effectiveness of all available treatments for neck pain; 2) to translate research evidence to clinical setting; 3) to identify the effectiveness of education and self-care in prevention and treatment of neck pain; 4) to identify casual factors for the development of neck pain 5) to define the natural course and prognostic factors for people with neck pain. The majority of the participants also considered the low back pain research priorities as neck pain research priorities, however the rank of importance of the items was considered different. Discussion and conclusions: A new research priorities agenda was developed through a consensus process from an active group of primary care-focused neck pain researchers. This research priorities agenda can be used as a guide to researchers and funding agencies to better conduct further research in the field of neck pain.